Magnetic order in functional iron oxides - Chmiel, F (2018)
Developing our understanding of the magnetic order of iron oxides is essential if we are to devise novel, functional magnetic memory devices and sensors. In this thesis we report on the magnetic order of the newly synthesised Y-type hexaferrite Ba0.5Sr1.5Mg2Fe12O22 (BSMFO) and on the remarkable domain morphology of the archetypal iron oxide Fe2O3. The magnetic phase diagram of BSMFO is studied by lab based characterisation methods and synchrotron techniques. We reveal a series of metastable magnetic structures, characterised by a period commensurate with the crystallographic lattice. We confirm this system is polar below 100 K and exhibits the worlds largest magnetoelectric effect. We perform a Resonant X-ray Diffraction (RXD) experiment to study this effect and show that RXD is sensitive to the magnetic polarity of BSMFO, the order parameter which drives the large magnetoelectric effect observed in this system. Using RXD microdiffraction, we spatially resolve the magnetic polarity domain configuration of BSMFO for the first time. When complemented by dynamic polarisation analysis of the scattered X-ray beam, these results allow us to propose a microscopic mechanism describing the large magnetoelectric effect observed in BSMFO. The RXD techniques demonstrated in this thesis open up a previously unexplored avenue for effectively studying the field-induced phases of the Y-type hexaferrites. The coupled domain structure of a α-Fe2O3/Co heterostructure is imaged using vector-mapped X-ray PhotoEmission Electron Microscopy. Our measurements reveal an unprecedented network of vortices in the antiferromagnetically ordered α-Fe2O3 layer which imprint, by exchange proximity, into the adjacent Co layer. This work represents the first observation of antiferromagnetic spin vortices in a laterally unconstrained system. These vortices are consistent with the Kibble-Zurek mechanism, originally conceived in the context of cosmology, which describes the formation (and preservation) of topological defects when cooling through a symmetry breaking phase transition. The topological nature of these vortices is exploited to control the domain configuration of our heterostructure by inducing mass vortex-antivortex annihilation. As well as being a suitable system to test the universality of the Kibble-Zurek mechanism, the network of vortices observed in this work have the potential to be incorporated into novel, highly efficient magnetic memory devices.